International financial statement analysis - Robinson, Thomas R. (CFA Institute investment series, 2012)
Up-to-date information on using financial statement analysis to successfully assess company performance, from the seasoned experts at the CFA Institute Designed to help investment professionals and students effectively evaluate financial statements in today's international and volatile markets, amid an uncertain global economic climate, International Financial Statement Analysis, Second Edition compiles unparalleled wisdom from the CFA in one comprehensive volume. Written by a distinguished team of authors and experienced contributors, the book provides complete coverage of the key financial f.